A combination of SILAC and nucleotide acyl phosphate labelling reveals unexpected targets of the Rsk inhibitor BI-D1870. Issue 1 (31st January 2014) - Edgar, Alexander J.; Trost, Matthias; Watts, Colin; Zaru, Rossana
Abstract : Protein kinase inhibitors frequently have interesting effects that cannot be fully ascribed to the intended target kinase(s) but identifying additional targets that might explain the effects is not straightforward. By comparing two different inhibitors of the Rsk (p90 ribosomal S6 kinase) kinases, we found that the increasingly used compound BI-D1870 had biological effects in murine DCs (dendritic cells) that could not be solely ascribed to Rsk or other documented targets. We assessed the ability of BI-D1870 and a second Rsk inhibitor, BIX 02565 to protect enzyme active sites from reaction with biotinylated nucleotide acyl phosphates. Using SILAC (stable isotope labelling by amino acids in cell culture)-labelled DC lysates as a source of enzyme targets, we identify several kinases that interact with BI-D1870 but not with BIX 02565. We confirmed that these kinases, including Slk, Lok and Mst1, are inhibited by BI-D1870 but to a much lesser extent by BIX 02565 and that phosphorylation of some of their substrates is blocked by BI-D1870 in living cells. Our results suggest that the BI-D1870 inhibitor should be used with caution. The SILAC-based methodology we used should be useful for further comparative unbiased profiling of the target spectrum of kinase inhibitors with interesting biological effects under conditions that closely mimic those found in cells.